Effect of sea water and MgSO4 solution on the mechanical properties and durability of self-compacting mortars with fly ash/silica fume - Benli, Ahmet; Karatas, Mehmet; Gurses, Elif (Elsevier Sci Ltd, 2017)
This experimental study was carried out to investigate the mechanical properties of self-compacting mortars (SCMs) containing binary and ternary mixtures of silica fume (SF) and fly ash (FA) immersed in sea water and 10% by weight magnesium sulfate (MgSO4) solution. 14 series of mortar specimens including control mixture were prepared by replacing Portland cement with 10%, 20% and 30% by weight of C class fly ash (FA) and 6%, 9%, 12% and 15% by weight of silica fume (SF). Ternary mixes were produced by replacing 10% of FA containing 6%, 9%, 12% and 15% of SF and 20% replacement of FA with 6% and 9% of SF. A total of 182 samples of 40 x 40 x 160 mm mortar were prepared and cured in water at 3, 28, 56 and 180 days and immersed in sea water and magnesium sulfate (MgSO4) solution at 28, 56, 90 and 180 days to observe SCMs behavior in hardened conditions. Durability properties were evaluated by capillary absorption (sorptivity and porosity tests). Mini slump flow diameter, viscosity and mini V-funnel flow time tests were performed to assess the fresh properties of SCMs containing FA and SF. The results showed that all binary and ternary mixes of SCMs and control specimens exposed to MgSO4 solution have increasing compressive and tensile strength up to 90 days then tend to decrease at the age of 180 days. The control specimens exposed to sea water showed the best resistance in terms of tensile strength. Porosity of SF binary blended SCMs cured in water at 28 days have higher values than ternary blended SCMs and the control specimens cured in water at 28 days have the lowest porosity. The SCMs exposed to magnesium sulfate solution, some deterioration such as crack formation due to surface softening was observed. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Self-compacting mortar; Silica fume; Fly ash; Magnesium sulfate; Seawater; Fresh properties; Mechanical properties; Durability